Many eyes on the ground: citizen science is an effective early detection tool for biosecurity - Thomas, M.; Gunawardene, Nihara; Horton, K.; Williams, A.; O Connor, S.; McKirdy, S.; van der Merwe, J. (Springer, 2017)
Early detection of target non-indigenous species is one of the most important determinants of a successful eradication campaign. For early detection to be successful, and provide the highest probability of achieving eradication, intense surveillance is often required that can involve significant resources. Volunteer based monitoring or “citizen science” is one potential tool to address this problem. This study differs from standard citizen science projects because the participants are personnel or contractors of a company working on Barrow Island, Western Australia. We show that personnel can contribute successfully to a surveillance program aimed at detecting a broad taxonomic range of non-indigenous vertebrate and invertebrate species. Using data collected over a five year surveillance period on Barrow Island, we show that eighteen of the nineteen (95%) non-indigenous invertebrate species new to the island were detected by personnel working on the island, and that the number of detections made by these workers was significantly related to the number of personnel on the island at any one time. Most personnel detections (91%) were made inside buildings where the majority of active surveillance tools could not be implemented. For vertebrates, 4 NIS species detections (100% of detections) were made in the built environment by personnel. Although reporting of suspect non-indigenous species is voluntary, personnel are required to attend inductions and toolboxes where reporting of suspect biosecurity risk material is encouraged. These results demonstrate the value of industry led ‘citizen science’ programs, resulting in sustained stewardship and conservation of areas with high environmental value.